Effect Of Service Quality On Consumer Loyalty With Consumer Satisfaction As An Intervening Variable At PT. Capella Dinamik Nusantara (Capella Honda 88 Workshop) Pekanbaru (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to determine the influence of service quality on consumer loyalty with consumer satisfaction as an intervening variable at PT. Capella Dinamik Nusantara (Capella Honda 88 Workshop) Pekanbaru. Methodology: In this study, a purposive sampling technique was used to sample 100 respondents. The method used was descriptive statistics with a quantitative approach. Measurement models, structural models, and hypothesis testing with SmartPLS4 software analyze data with a Likert scale. Results: the results show that service quality has a significant direct effect on consumer loyalty with a T-statistic of 2.388>1.96 and a p-value of 0.0171.96 and a p-value of 0.0001.96. and the p-value 0.0001.96 and a p-value of 0.000